COMPARATIVE ANALYSIS OF VEHICLES AND STATIONARY SOURCES IMPACT ON THE ATMOSPHERE IN A BIG CITY - Kuren, S. G.; Gudenko, N. E. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2019)
The paper provides the analysis of the results of a multi-year monitoring of pollutant emissions from motor vehicles and stationary sources recorded in Rostov-оn-Don. Conclusions on the composition, structure and scope of these emissions are drawn. The authors prepared a database covering 2009-2016 years to build mathematical models of atmospheric air pollution.